Critical Cases of the π-Stability of a Nonautonomous Quasilinear Equation of the nth Order - Vitrychenko, I. E. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We establish sufficient conditions for the π-stability of the trivial solution of a quasilinear equation of the nth order.